2022
DOI: 10.1136/bmjopen-2021-055226
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider’s perspective on barriers and facilitators for medication adherence among adult patients with cardiovascular diseases and diabetes mellitus in India: a qualitative evidence synthesis

Abstract: ObjectiveTo explore the various stakeholders’ perspectives on barriers and facilitators for medication adherence among patients with cardiovascular diseases (CVDs) and diabetes mellitus (DM)in India.DesignSystematic review of qualitative studies.Data sourcesA comprehensive systematic search was conducted in Medline, Cochrane Library, Science Direct and Google Scholar from January 2010 to July 2020. We included all qualitative peer-reviewed studies, reporting barriers and facilitators of medication adherence, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
2
17
0
1
Order By: Relevance
“…This study found many barriers to successful treatment adherence. Individual and contextual barriers included the physical problems to do regular physical activity, complications of diabetes, forgetting to take medicines, high cost and low insurance coverage of medicines, doctor visits and lab tests, and low availability of drugs especially insulin, and this is consistent with international studies (Huang & Shiyanbola, 2021;Krishnamoorthy et al, 2022;Rezaei et al, 2019). In Iran, as suggested by the NPPCD and the NGOs, such as the Iranian Diabetes Society, there are different ways to promote the perceived benefits of treatment adherence and overcome the potential barriers.…”
Section: Discussionsupporting
confidence: 74%
“…This study found many barriers to successful treatment adherence. Individual and contextual barriers included the physical problems to do regular physical activity, complications of diabetes, forgetting to take medicines, high cost and low insurance coverage of medicines, doctor visits and lab tests, and low availability of drugs especially insulin, and this is consistent with international studies (Huang & Shiyanbola, 2021;Krishnamoorthy et al, 2022;Rezaei et al, 2019). In Iran, as suggested by the NPPCD and the NGOs, such as the Iranian Diabetes Society, there are different ways to promote the perceived benefits of treatment adherence and overcome the potential barriers.…”
Section: Discussionsupporting
confidence: 74%
“… 21 , 22 , 23 , 24 , 25 Lack of dietary control, regular physical exercise, glucose testing, and medication adherence are common in India. 26 , 27 , 28 , 29 We found that environmental barriers were common in our setting, particularly among people with low levels of formal education. Most of the prior Indian studies have identified similar findings coupled with inadequate counselling from the health care system.…”
Section: Discussionmentioning
confidence: 77%
“…Another study conducted in Uzbekistan, on 209 patients, revealed that 36.8% of the patients had a low level of adherence; knowledge regarding the disease was significantly associated with low medication adherence [ 17 ]. A study conducted in India in 2022 revealed that medication adherence was 20.83%, 28.37%, and 32% in hypertension (HTN), congestive cardiac failure (CCF), and ischemic heart disease (IHD) patients, respectively [ 18 ]. A study conducted in rural India on 280 patients revealed that about 32% of the patients had low adherence [ 19 ].…”
Section: Discussionmentioning
confidence: 99%